The Relationship Between Nutritional Status And The Development Of Children Aged 4-60 Months - Yuningsih Yuningsih; Ai Nur Zannah; Asri Iman Sari; Ririn Handayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Child development is an important aspect of human life, especially in the early period of life, which is often referred to as the critical or golden period as the child's brain undergoes rapid growth. Developmental disorders in children under five, especially in terms of motor skills, have a long-term impact on their development, and a child's nutritional status has been shown to play a role in the process. Therefore, this study aims to determine the relationship between nutritional status and development of children aged 4-60 months in Jember Regency. The research method used was a quantitative correlational approach with a cross-sectional approach, involving a total of 57 children who had a Kartu Menuju Sehat (KMS) as the population. From the results of the formula calculation, the sample size was determined as 50 respondents using a non-randomized (non-probability) method, namely purposive sampling based on certain criteria. The research instruments involved the Kartu Menuju Sehat (KMS) to assess children's nutritional status and the Developmental Pre-Screening Questionnaire (KPSP) to identify children's development. The results of the chi-square statistical test revealed a significant relationship between nutritional status and development of children aged 4-60 months in Jember District. [ Children with good nutritional status show more optimal developmental progress, while children with poor nutritional status tend to experience slower or inappropriate development for their age. This finding supports theories that emphasize the importance of adequate nutrition for children's growth and development. Therefore, efforts to improve children's nutritional status should be a top priority in various child health and education programs. With the right understanding and action, we can help create a healthier and more potential future generation.